Shamanism and the Manchu Bannermen of the Qing Dynasty - Xiaoli Jiang (Religions, 2022)
With the Qing armies marching into Beijing through the Shanhai Pass, the Manchu bannermen under the Eight Banners system saw great changes in their everyday lives. However, they continued with the practice of shamanic sacrifices. This paper analyzes the “Sacred Books”, genealogies, and other historical materials about shamanic rituals, to place shamanism in the lives of the bannermen of the Qing Dynasty. It explores the relationship between this religion and the lives of Manchu bannermen, their clan organizations, and their livelihoods. The paper helps strengthen our understanding of shamanism that continued to flourish during the Qing Dynasty by playing a vital role in the lives of Manchu bannermen.